Magnetic flux noise in the three Josephson junctions superconducting ring - Il’ichev, E.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We analyze the influence of noise on magnetic properties of a superconducting loop which contains three Josephson junctions. This circuit is a classical analog of a persistent current (flux) qubit. A loop supercurrent induced by external magnetic field at the presence of thermal fluctuations is calculated. In order to get connection with experiment we calculate the impedance of the low-frequency tank circuit which is inductively coupled with a loop of interest. We compare obtained results with the results in quantum mode — when the three junction loop exhibits quantum tunneling of the magnetic flux. We demonstrate that the tank-loop impedance in the classical and quantum modes have different temperature dependence and can be easily distinguished experimentally.